Clinical practice guideline for the screening and management of the mild depressive episode at the first level of care for the Peruvian Social Security (EsSalud) - Macciotta-Felices, Beatrice (2020)
This paper summarizes the clinical practice guide (CPG) for the screening and management of mild depressive episode at the first level of care in the Social Security of Peru (EsSalud). A guideline development group (GDG) was established for develop this CPG, which included clinical and methodology specialists, who formulated 06 clinical questions. Systematic searches were conducted in Pubmed and GPC repositories to answer each question, and relevant evidence was selected. The certainty of the evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. In periodic work meetings, the GDG used the GRADE methodology for reviewing the evidence and for developing recommendations. At the end, this CPG formulated 07 recommendations (03 strong and 04 conditional), 28 points of good clinical practice, and 02 flow charts were formulated.